THU0030 Evidence for good intrinsic mesenchymal stem cell activity in gelatinous heberden's nodes in osteoarthritis at clinical presentation. (23rd January 2014) - Baboolal, T.; Boxall, S.; Buckley, C.; Tan, A.L.; Churchman, S.; Calder, S.; Kouroupis, D.; Giannoudis, P.; Hodgson, R.; Jones, E.; McGonagle, D.
Abstract : Background: Heberden's nodes (HN) are common pre-radiographic features of generalised osteoarthritis (GOA) and they may present as acute cystic lesions before eventually leading to florid new bone formation [1]. Objectives: To examine if the gelatinous material from Heberden's nodes "synovial cysts" contained multipotential mesenchymal stromal cells (MSCs), and whether such cells were of bone marrow or synovial fluid origin and to link the findings to joint structure especially articular cartilage integrity. Methods: Two patients with clinical OA having Heberden's nodes in their distal interphalangeal (DIP) joint at clinical presentation were imaged with conventional x-ray and high resolution MRI to ascertain the extent of joint involvement. Gelatinous material from the synovial cysts was extruded and plastic-adherent cells were expanded in MSC conditions and characterised phenotypically and functionally utilising trilineage differentiation assays. Mesenchymal related gene expression was studied using a Custom Taqman Low Density Array (69 Genes) to determine the underlying origin and molecular profile of the cells. Results: Imaging showed that one case had excellent articular cartilage preservation but had osteophyte formation, whilst the other case had more extensive joint damage. The HN material formed MSC-like colonies, displayed an MSC phenotype being negative for CD14, CD19, CD31, CD34, CD45 and HLADR, and positive for CD29, CD44, CD73, CD90, CD105 and CD166. Functionally these cells exhibited osteogenic, adipogenic and chondrogenic lineage differentiation. Gene cluster analysis showed that HN-MSCs were more closely related to synovial fluid (SF-) than to bone marrow (BM-MSCs) with much higher expression of SFRP4 (Secreted Frizzled-Related Protein 4), a newly identified synovium/SF-MSC marker [2]. Conclusions: This is the first description of a resident population of MSCs in a small joint in which, we show their presence in acute Heberden's nodes. The presence of these MSCs even in cases where there is good preservation of articular cartilage indicates Heberden's node stem cell activity may be a key early event in hand OA pathogenesis. References: Kellgren JH, Moore R. Generalized osteoarthritis and Heberden's nodes. Br Med J 1952;1:181-7. Sekiya I, Ojima Ml. Human mesenchymal stem cells in synovial fluid increase in the knee with degenerated cartilage and osteoarthritis. J Orthop Res 2011. Epub 2011/12/08. Disclosure of Interest: None Declared